(untitled) (PANGEEA, 2025)
This paper aims to channel some ideas on an unique path of topographical inventory data of archaeological site through designing and managing a computerized database corresponding to some pilot archaeological site (Puţul Tătarului), useful and applicable nationwide, out of which the topo-archaeological information may result quickly and securely, according to the research objectives.